Pengembangan Perangkat Pembelajaran Terpadu Model Webbed Melalui Pendekatan Tematik Di TK - Rosnawati Rosnawati; Tanjung Nia Sari (UIN Sultan Maulana Hasanudin Banten, 2021)
The objectives of this study include: (1) to find out how a thematic approach is used in the development of integrated learning using the webbed model, which focus on the concept of learning by doing in kindergarten; (2) to determine the effectiveness of the web-based integrated learning model using a thematic approach that focus on the concept of learning through early childhood learning; (3) to create a valid Webbeb learning model using the learning-by-doing concept. The method in this study is a research and development approach. The results of this study include: (1) the development of this teaching tool is based on research and development theory that focuses on creating a teaching device so that learning is not monotonous, draws children’s attention to learning, so that learning is more meaningful, because children are more proactive in problem solving using their real experiences; (2) Webbeb learning model, based on a thematic approach through a learning-by-doing concept, is effective for classroom learning because it focuses on learners so that learners find their own material concepts by focusing on the school environment; and (3) a web-integrated learning model using a thematic approach through a learning-by-doing concept that was created after validation by a multi-custom validator.